Implementasi Deep Learning dalam Pembelajaran Matematika yang Bermakna di Sekolah Dasar - M. Agung Alwanda; Rizki Saputra (MAN 4 Kota Pekanbaru, 2026)
This study examines the implementation of a deep learning approach in meaningful mathematics learning at the elementary school level. The research aims to analyze how deep learning principles are integrated into mathematics instruction, identify strategies aligned with the Kurikulum Merdeka, and explore challenges and solutions in its application. Using a Systematic Literature Review (SLR) guided by the PRISMA protocol, 903 documents were identified, and 13 articles met the final inclusion criteria. The findings show that meaningful, mindful, and joyful learning principles are consistently embedded through contextual activities, problem-based and project-based learning, reflective practices, and digital media integration. Deep learning effectively enhances students’ conceptual understanding, critical thinking, and engagement. However, limitations remain in teacher readiness, digital infrastructure, time allocation, and assessment practices. The study highlights the potential of deep learning to transform mathematics learning while recommending more empirical classroom studies and long-term evaluations to strengthen its pedagogical implementation.